PRKCI Mediates Radiosensitivity via the Hedgehog/GLI1 Pathway in Cervical Cancer - Wu, Zhuna; Huang, Chunxian; Li, Ruixin; Li, Hui; Lu, Huaiwu; Lin, Zhongqiu (Frontiers in Oncology, 2022)
Objective. Insensitivity to radiotherapy accounts for the majority of therapeutic failures in cervical cancer (CC) subjects who undergo radical radiotherapy. We aimed to detect the probable molecular mechanisms of radiosensitivity to find methods to improve the overall 5-year survival rate. The atypical protein kinase Cι (aPKCι) gene PRKCI exhibits tumor-specific copy number amplification (CNA) in CC. We concentrated on how PRKCI decreases radiosensitivity in CC and assessed the interplay between PRKCI and the Hedgehog (Hh)/Gli1 pathway in the present research. Methods. The biological functions of PRKCI in CC radiosensitivity were ex-plored through IHC, colony formation, CCK-8, cell cycle, and apoptosis assays and xenograft models. qRT-PCR, Western blot analysis and immunofluorescence assays were utilized to evaluate the interplay between PRKCI and the Hh/Gli1 pathway and its mechanism on PRKCI-decreased radiosensitivity in CC. Furthermore, auranofin (AF), a selective inhibitor of PKCι, was explored through biochemical assays in CC cells in vitro and in vivo. Result. We found that high PRKCI expression was in charge of decreased sur-vival in CC. PRKCI was noticed to be intimately allied with radiation-triggered al-terations in proliferation, the cell cycle, apoptosis and xenograft growth. The Hh/Gli1 pathway was initiated when PRKCI expression was altered. PRKCI func-tions downstream of Hh/Gli1 pathway to phosphorylate and activate the transcrip-tion factor Gli1. Auranofin (AF) act as radiosensitizer displayed biological functions in vitro and in vivo. Conclusions. PRKCI is an underlying therapeutic target for regulating radio-sensitivity in CC. It regulates radiosensitivity by modulating Gli1 relocalization and phosphorylation in CC via the Hh/Gli1 pathway.